Consumers’ Preference for User-Designed Versus Designer-Designed Products: The Moderating Role of Power Distance Belief - Song, Xiaobing; Jung, Jihye; Zhang, Yinlong (Journal of Marketing Research, 2021)
Anecdotal evidence and extant research show that consumers can prefer both user-designed and designer-designed products. However, the factors that moderate such preferences are not well understood. The authors posit power distance belief (PDB) as a moderator such that low-PDB consumers prefer user-designed to designer-designed products because they identify more with user-driven companies. In contrast, high-PDB consumers prefer designer-designed to user-designed products due to their stronger trust in designer-driven companies. Six studies examining power distance belief at both the country and individual levels provide convergent support for the proposed moderating effect of PDB and underlying mechanisms. Furthermore, the authors demonstrate that the interaction between design philosophy and PDB is more likely for low-complexity than high-complexity products.